A critical and comparative appraisal of polycyclic aromatic hydrocarbons in sediments and suspended particulate material from a large South American subtropical estuary. (July 2016) - Cardoso, Fernanda D.; Dauner, Ana Lúcia L.; Martins, César C.
Abstract: The Paranaguá Estuarine Complex (PEC) is an important socioeconomic estuary of the Brazilian coast that is influenced by the input of pollutants like polycyclic aromatic hydrocarbons (PAHs). Because of the apparent lack of comparative studies involving PAHs in different estuarine compartments, the aim of this study was to determine and compare PAH concentrations in surface sediment and suspended particulate material (SPM) in the PEC to evaluate their behaviour, compositions, sources and spatial distributions. The total PAH concentrations in the sediment ranged from 0.6 to 63.8 ng g −1 (dry weight), whereas in the SPM these concentrations ranged from 391 to 4164 ng g −1 . Diagnostic ratios suggest distinct sources of PAHs to sediments (i.e., pyrolytic sources) and SPM (i.e., petrogenic sources such as vessel traffic). Thus, the recent introduction of PAHs is more clearly indicated in the SPM since oil related-compounds (e.g., alkyl-PAHs) remain present in similar concentrations. Further, this matrix may better reflect the current state of the environment at the time of sampling because of the absence of significant degradation. Graphical abstract: Highlights: PAH content was determined in surface sediment and suspended particulate material. SPM showed a petrogenic contamination, which was not observed in surface sediment. Environmental monitoring of PAH should consider assessments of both sediment and SPM. Abstract : Distinct distribution of individual polycyclic aromatic hydrocarbon on suspended particulate matter and sediment occurred in a subtropical estuary.